(Invited) Electrochemical Characterization of Nanogap Interdigitated Electrode Arrays for Lab-on-a-Chip Applications. (25th October 2017) - Matylitskaya, Volha; Kasemann, S; Urban, G; Dincer, C; Partel, Stefan
Abstract : In this work we present recent results on electrochemical characterization of the fabricated nanogap interdigitated electrode arrays (nIDAs) for Lab-on-a-Chip applications. The advantages of the presented nIDAs and their potential for application in bioelectrochemistry were studied using different electrochemical methods. Chronoamperometry is applied to achieve reversible redox processes which lead to an amplification of the measured current compared to a single electrode configuration and as a result, an increase in signal-to-noise ratio. For the electrochemical characterization of the created nIDAs ferrocenemethanol (FcMeOH) and p-aminophenol (pAP) were selected as redox couples. An amplification factor above 160 was obtained with FcMeOH for the nIDAs with 100 nm gap. An inverse correlation between gap size and amplification was proven. In addition, the formation of a polymer film during redox cycling could be verified to cause the lower amplification factor observed in pAP measurements. Furthermore, different electrode cleaning procedures were demonstrated by combination of O2 plasma and cyclic voltammetry. The nIDAs presented here offer many advantages including low-cost fabrication, high amplification and collection factors and thus are highly suitable for biosensor applications.